Altered phenotype and function of natural killer cells expressing the major histocompatibility complex receptor Ly-49 in mice transgenic for its ligand. - Olsson, M Y (1995)
The Ly-49 molecule has been shown to interact with major histocompatibility complex (MHC) class I molecules, and the lytic function of Ly-49+ natural killer (NK) cells from C57BL/6 (H-2b) mice is inhibited by the recognition of H-2Dd on tumor target cells. Introduction of a Ly-49 ligand, H-2Dd, into C57BL/6 mice did not alter the percentage of Ly-49+ NK cells (13-18%), but it led to three functional effects on this subset. (i) The Ly-49 expression in the positive population was reduced by 30-50% compared to C57BL/6 control mice. (ii) While this Ly-49+ subset (Ly-49lo) in the transgenic mice failed to kill BALB/c concanavalin A (Con A) blasts, which have high H-2Dd expression, it was capable of killing SP2/0 tumor cells, which have low H-2Dd expression. Ly-49+ NK cells (Ly-49hi) from nontransgenic mice failed to kill both of these H-2Dd-expressing target cells. (iii) In the transgenic mice, the Ly-49+ subset acquired the ability to kill C57BL/6 Con A blasts, in contrast to the Ly-49+ NK cells of C57BL/6 mice. We propose a "receptor-calibration" hypothesis, where low receptor density on the effector cells imposed by selection or adaptation to the environment allows higher sensitivity for detection of reduced self-MHC ligands on potential target cells.